KECERDASAN SPIRITUAL, WORK-FAMILY CONFLICT, FAMILY-WORK CONFLICT, DAN KINERJA PADA PEKERJAAN DAN KELUARGA (STUDI PADA KARYAWAN PERBANKAN PONTIANAK) - Endang Dhamayantie (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2013)
The purpose of this research is to understanding the influence of spiritual intellegence on of both directions of work-family-conflict and family-work-conflict and performance on the work and family. Research done on female employees of the banking sector who have married in the city of pontianak A number of samples as much as 83 respondents are determined using the method of purposive sampling. Data was analyzed using regression with a standardized variable (path Anlysis) The result showed that 1)spiritual inteligence influence negatively to work-family conflict ; 2)spiritual intelegence influece negatively to family-work conflict; 3)work-family conflict influence negatively to family performence and 4) family-work conflict influence negatively to the work performence